Geostatics approach with indicator kriging for assesing groundwater vulnerablity to nitrate contamination - Muhammad Jamil, Rohazaini (2011)
In Malaysia, the demand for water has increased tremendously and groundwater has been identified as one of the alternative to new water sources. In north eastern state of Kelantan, Malaysia, almost 70 percents of people consumes groundwater in their daily lives. However, due to uncontrolled development and human activities, groundwater is subjected to pollution and geochemical contamination. This paper is intended to assess groundwater vulnerability to nitrate (NO 3) contamination using geostatistical approach with indicator kriging instead of using the typical DRASTIC (Depth, Recharge, Aquifer, Soil, Topography, Influence of the vadose zone and Conductivity) model. Geostatistical approach has the capability to predict and understand the geochemical concentration pattern as an alternative to the DRASTIC model which is unable to provide the measurable information of geochemical characteristics. The results of the modelling are produced and presented in the form of probability map using indicator kriging interpolation. The finding of the study can be used to identify the probability of geochemical concentration exceeding the specified threshold.